2023
DOI: 10.3390/biomedicines11020259
|View full text |Cite
|
Sign up to set email alerts
|

Propolis and Their Active Constituents for Chronic Diseases

Abstract: Propolis is a mass of chemically diverse phytoconstituents with gummy textures that are naturally produced by honeybees upon collection of plant resins for utilization in various life processes in beehives. Since ancient times, propolis has been a unique traditional remedy globally utilized for several purposes, and it has secured value in pharmaceutical and nutraceutical areas in recent years. The chemical composition of propolis comprises diverse constituents and deviations in the precise composition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 124 publications
0
18
0
Order By: Relevance
“…Similar results were observed when the 12 specific flavonoids and phenolic acids were evaluated, while their peak areas of were noted as Table 3. As noted, except for some resin‐like macromolecules, the main active components of propolis are typical small molecular natural products [21,25] . Considering the filtration efficiency and product yield, our data indicated that MWCO 30 KDa was the optimum format to filtrate propolis alcoholic extracts and we used this for subsequent experiments.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Similar results were observed when the 12 specific flavonoids and phenolic acids were evaluated, while their peak areas of were noted as Table 3. As noted, except for some resin‐like macromolecules, the main active components of propolis are typical small molecular natural products [21,25] . Considering the filtration efficiency and product yield, our data indicated that MWCO 30 KDa was the optimum format to filtrate propolis alcoholic extracts and we used this for subsequent experiments.…”
Section: Resultsmentioning
confidence: 75%
“…As noted, except for some resinlike macromolecules, the main active components of propolis are typical small molecular natural products. [21,25] Considering the filtration efficiency and product yield, our data indicated that MWCO 30 KDa was the optimum format to filtrate propolis alcoholic extracts and we used this for subsequent experiments. Deserve to be mentioned, the filtrated material is cleaner than the original one.…”
Section: A Mwco 30 Kda Membrane Provides Satisfied Results Following ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In such a situation nanomedicine makes a good case that can be utilized to solve the issues with conventional CT related to drug delivery, distribution, and compatibility. And with advancements in nanomedicine approaches like theranostics can be utilized to diagnose and therapeutically treat the tumor with high accuracy [4,5]. Thus, the use of nanoparticles in the diagnosis and treatment of cancer is clubbed under the term "Nanotheranostics".…”
Section: Introductionmentioning
confidence: 99%
“…Propolis colour varies reddish green to brown and has characteristically odour (Silici 2019). The components of propolis are resins (50 %); wax (30 %); volatile essential oils (10 %); pollen grains (5 %) consequently includes more than 100 compounds as fenolic acids and esters, flavonoids and terpenoids and this combines have antiviral, antifungal, anti-inflammatory, antibacterial, antiparasitic, immunomodulatory and hepatoprotective properties (Kujumgiev et al 1999;Gao et al 2014;Mahmoud and Rizk 2014;Chen et al 2018;Lisbona-Gónzalez et al 2021;Lopez-Válverde et al 2021;Sahlan et al 2021;Santos et al 2021;Asma et al 2022;Chavda et al 2023). Propolis is effective in cleaning the cells of the honeycomb, the development of the egg laid by the queen bee in a sterile environment and the protection of the brood besides, bees working inside the hive, prevent various infections from entering the hive by brushing the worker bees coming from outside that infected various microorganisms during foraging, with propolis at the hive entrance hole (Kumova et al 2002).…”
Section: Introductionmentioning
confidence: 99%